Etnobotani Tumbuhan Obat Tradisional Di Desa Piliana Dan Desa Hatu Kecamatan Tehoru Kabupaten Maluku Tengah - Kiat, Fatwa A.; Puttileihalat, Maya M.S.; Sahusilawane, John F. (MAKILA, 2019)
This study aims to determine the ethnobotany of medicinal plants in Piliana Village and Hatu Village, Tehoru District, Central Maluku Regency. This research took place from February 2019. In connection with the implementation of this research, the method used is the purposive sampling method. Data is all information or material provided that must be sought and collected by the problem being studied. The data used in this study include primary data and secondary data. In this study, data collection in the form of interviews with the community was also carried out by determining the sample in the field of 10% of the number of families (heads of families). In addition to interviews to get in-depth results, observation and documentation are also carried out so that the data obtained is more accurate by the data obtained at the research time. There are 71 types of medicinal plants found in Piliana and Hatu villages; 48 ​​types of diseases are treated. Most of the plant organs used are leaves, and the most commonly used processing method is boiling. There are 21 different plant species found in Piliana Village and 29 medicinal plants in Hatu Village.